Escherichia coli Strains Producing Selected Bacteriocins Inhibit Porcine Enterotoxigenic Escherichia coli (ETEC) under both In Vitro and In Vivo Conditions - Hrala, Matěj; Bosák, Juraj; Micenková, Lenka; Křenová, Jitka; Lexa, Matej; Pirková, Viktória; Tomáštíková, Zuzana; Koláčková, Ivana; Šmajs, David (Applied and environmental microbiology, 2021)
Enterotoxigenic Escherichia coli (ETEC) and Shiga toxin-producing E. coli (STEC) strains are the causative agents of severe foodborne diseases in both humans and animals. In this study, porcine pathogenic E. coli strains (n = 277) as well as porcine commensal strains (n = 188) were tested for their susceptibilities to 34 bacteriocin monoproducers to identify the most suitable bacteriocin types inhibiting porcine pathogens. Under in vitro conditions, the set of pathogenic E. coli strains was found to be significantly more susceptible to the majority of tested bacteriocins than commensal E. coli. Based on the production of bacteriocins with specific activity against pathogens, three potentially probiotic commensal E. coli strains of human origin were selected. These strains were found to be able to outcompete ETEC strains expressing F4 or F18 fimbriae in liquid culture and also decreased the severity and duration of diarrhea in piglets during experimental ETEC infection as well as pathogen numbers on the last day of in vivo experimentation. While the extents of the probiotic effect were different for each strain, the cocktail of all three strains showed the most pronounced beneficial effects, suggesting synergy between the tested E. coli strains. IMPORTANCE Increasing levels of antibiotic resistance among bacteria also increase the need for alternatives to conventional antibiotic treatment. Pathogenic Escherichia coli represents a major diarrheic infectious agent of piglets in their postweaning period; however, available measures to control these infections are limited. This study describes three novel E. coli strains producing antimicrobial compounds (bacteriocins) that actively inhibit a majority of toxigenic E. coli strains. The beneficial effect of three potentially probiotic E. coli strains was demonstrated under both in vitro and in vivo conditions. The novel probiotic candidates may be used as prophylaxis during piglets' postweaning period to overcome common infections caused by E. coli.
Keywords: infekce vyvolané Escherichia coli; Escherichia coli Infections; feces; Swine Diseases; Escherichia coli; zvířata; faktory virulence; Swine; Feces; Bacteriocins; Bacterial Toxins; prasata; nemoci prasat; probiotika; Animals; bakteriální toxiny; Probiotics; Virulence Factors; bakteriociny